2007
DOI: 10.1002/jor.20388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of femoral cortical bone following cemented hip replacement

Abstract: Femoral bone remodeling following total hip replacement is a big concern and has never been examined mechanically. In this study, six goats underwent unilateral cemented hip hemiarthroplasty with polymethyl methacrylate (PMMA) bone cement. Nine months later animals were sacrificed, and the femoral cortical bone slices at different levels were analysed using microhardness testing and microcomputed tomography (micro-CT) scanning. Implanted femurs were compared to contralateral nonimplanted femurs. Extensive bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The hardness of a material has been defined as its resistance to penetration by an indenter 42 . Vickers microhardness test was performed using a HMV-2T microhardness test machine fitted with a pyramidal diamond indenter (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardness of a material has been defined as its resistance to penetration by an indenter 42 . Vickers microhardness test was performed using a HMV-2T microhardness test machine fitted with a pyramidal diamond indenter (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Vickers microhardness test was performed using a HMV-2T microhardness test machine fitted with a pyramidal diamond indenter (Shimadzu, Japan). Method was described previously 42 . Briefly, a mass of 40 g was used throughout the test.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical properties of the vertebrae (L5) were evaluated following our previously established protocols . Briefly, the compression test was performed using a servo‐hydraulic material testing machine (MTS System, Inc., Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…The degree of preferential BAp orientation is related to bone mechanical function, and reduced orientation is an important contributor to reduced bone mechanical function. 7,22) In fact, Ni et al 23) reported that the micro-hardness in the region proximal to the artificial hip joint is 20% lower than that on the non-implanted side. This may suggest that the change in the degree of BAp orientation is involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%